Relegating expertise: The outward and inward positioning of librarians in information literacy education. (September 2022) - Hicks, Alison; Lloyd, Annemaree
Previous research has demonstrated that professional narratives reference discourses that shape the practice of information literacy within higher education. This article uses discourse analysis method to identify how information literacy discourses construct and position teaching librarians within higher education. Texts analysed include four recent English-language models of information literacy and 16 textbooks. Analysis suggests the existence of two distinct narratives related to the role, expertise and professional practice of teaching librarians. In the outward-facing narrative librarian work is typically absent from guidelines for practice. In contrast, book introductions, which constitute the inward-facing narrative, centre professional librarians yet simultaneously position them as incompetent, or as lacking the skills and understandings that they need to be effective in this setting. These narratives constitute a form of othering that threatens professional practice at a time when the professionalisation of librarianship is being drawn into question. This article represents the second in a research programme that interrogates the epistemological premises and discourses of information literacy within higher education.